IoT Based Health Monitoring System with LoRa Communication Technology - Misran N.; Islam M.S.; Beng G.K.; Amin N.; Islam M.T. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electrocardiography; Health care; Monitoring; Oxygen; Communication technologies; Confidence interval; Emergency situation; Health care costs; Health care professionals; Health monitoring system; Oxygen saturation; Wireless platform; Internet of things